Micro-organismos marinhos produtores de metabólitos secundários biologicamente ativos - Sousa, Thiciana da Silva (2013)
This work describe the chemical and biological investigation of the extracts from the marine bacterias Pseudoalteromonas sp., Micromonospora sp., Streptomyces sp. and Kocuria sp., aiming the isolation and structural elucidation of new bioactive constituents. The chemical investigation carried out with the bacteria Pseudoalteromonas sp. lead to the isolation a red pigment identified as prodigiosin and two bile acids derivatives known as deoxycholic acid and cholic acid. The prodigiosin was evaluated against four tumor cell lines showing IC50 values similar to the positive control doxorubicin. The chemical study of Micromonospora sp. Resulted in the isolation of four new anthracyclinones designed as 4,6,11-trihydroxy-9-propryltetracene-5,12-dione; 4-methoxy-9-propyltetracene-6,11-dione; 7,8,9,10 - tetrahydro-9-hydroxy-4-methoxy-9-propiltetra-cene-6,11-dione and 10β-Carbomethoxy-7,8,9,10-tetrahydro-4,6,7α,9α,11-pentahydroxy-9-propyltetracene-5,12-dione . The cytotoxic potential of these compounds were evaluated against HCT-8cell line, two of which showed moderate cytotoxicity with IC50 values of 12.74 and 6.18 M, respectively. From Streptomyces sp. strain was isolated a ditiolpyrrolidin, established as 5-oxo-6-(N-methylformamide) -4,5 - dihydro-1,2-dithiol [4,3-b] pyrrole. This secondary metabolite was tested against six tumor cell lines, shown IC50 values of 1.66, 1.05 and 1.52 mM for the metastatic prostate lines, ovarium carcinoma and glioblastoma, respectively. The study of Kocuria sp. lead to the isolation of a new peptide, which was designed as kocurin. This compound was subjected to the tested its antimicrobial assays against several pathogens bacteria and fungal including Staphylococcus aureus strains methicillin resistant (MRSA) and Staphylococcus aureus strains tiazomicin resistant. Kocurin was strongly active against MRSA MB5393 exhibiting a MIC of 0,25µg/mL, moreover showed antibacterial activity against Bacillus subtilis and Enterococcus faecium. The structures of all isolated compounds in this work were stabilized employing spectroscopic methods such as 1H and 13C NMR (1D and 2D), mass spectrometry and infrared.